Biossorção do corante têxtil reativo azul 5G comparando resíduos industriais casca de soja e serragem - Goedert, Bruna dos Santos Cunha (2017)
The textile industry is responsible for the disposal of great volumes of wastewaters, which contain high organic content and, notably, highly visible coloration. The diversity of chemical products used in the process, such as synthetic dyes, make the effluent variable and difficult to treat. Different methods are used for textile wastewaters treatment, such as adsorption, whereas the use of biossorbents constituted by agro-industrial waste is an alternative to the decontamination of such effluents. As such, the purpose of this study was to evaluate the potential of the utilization of the industrial wastes Soybean Hull and Sawdust as alternative adsorbents in the biossorption of textile dye Reactive Blue 5G in synthetic aqueous solution. The Granular Activated Carbon (GAC) was also tested as a comparison, in the same conditions of the proposed biossorbents. In order to do so, the biomass were characterized and the effects of pH, chemical treatment and material granulometry were evaluated, and finally, the adsorption runs were carried out, in which the process’ kinetics, isotherm and thermodynamics were evaluated. The physicochemical and structural characterization of the biossorbents allowed to identify a low content of humidity, ashes, volatile organic matter, as well as a higher amount of acid groups. The preliminary tests indicated that the ideal conditions for the process were a pH 2 and a granulometry of the in nature biomatter of 1 to 2 mm. The time for the process to reach equilibrium was found to be 100 min and the maximum removal rates were 96, 97 and 88% for the soybean hull, sawdust and GAC, respectively. By applying the kinetic models, it was verified that the biossorption process is of chemical nature, since the pseudo-second order model presented the best fit. For the adsorption isotherms, the Langmuir and Redlich-Peterson models described properly the equilibrium experimental data, indicating maximum adsorption capacity of 29,272, 28,241 and 23,2 mg g-1 for the soybean hull (25°C), sawdust (45°C) and GAC (25°C), respectively. Therefore, based on the obtained results, it was concluded that the sawdust presented more favorable conditions for a full scale application in the adsorption of Reactive dye Blue 5G, in comparison to the soybean hull. This biossorbent presented more acid groups in its structure, a wider pH range in which adsorption is favored, higher removal efficiency, better affinity with the dye, as well as a more stable process regarding temperature variation. Also, it is possible to state that the biossorbents’ performance regarding the dye adsorption was better than the commercial adsorbent GAC, considering that equilibrium, as well as maximum removal rate, were achieved in lower time. Besides, the maximum adsorbed amount was higher for the soybean hull and for the sawdust. Thereafter, the results of this research suggest that the studied biossorbents present a good adsorption potential for the dye Reactive Blue 5G, and are a viable alternative for the textile wastewater treatment, since these materials present a natural source, high availability and low cost. The use of such materials as biossorbents allows better industrial waste management, thus providing environmental and economical benefits.